(untitled) (Revista da UFMG, 2012)
This article aims at presenting the project Lieux de Savoir, an innovative interdisciplinary theoretical entrepreneurship that distances itself from a limited, hierarchized and disciplinary notion of science to embrace a historical-anthropological oriented approach of human knowledge. From this perspective, the text highlights different practices of social production of knowledge in a more pluralistic perspective: as cognitive operations of production and dissemination of knowledge; as specific forms of social organization of space, communities and institutions; and as forms of social validation of knowledge and the consequent paradigms of knowledge that come out of these practices.